Efectos de la fertilización con macronutrientes sobre la absorción de cadmio de dos materiales genéticos de cacao (Theobroma cacao L.) utilizados como patrones, bajo condiciones controladas. - Pincay Ganchozo, Roger Alexander (2022)
With the objective of evaluating the effects of fertilization with macronutrients on the absorption of cadmium from two cocoa genetic materials (Theobroma cacao L.) used as standards. An experiment was carried out in the greenhouse of the Soil and Water Management Department of the Pichilingue Tropical Experimental Station of the National Institute of Agricultural Research. Under a randomized complete block design with divided plot arrangement. Using 14 treatments for three replications, the treatments were made up of two factors. Genotypes of factor A (CCN-51 and EET-103), factor B (fertilization). The variables that were evaluated at 45, 60, 75 and 90 days after sowing were: vigor index and chlorophyll index. At the end of the study, a destructive sampling was carried out and the following were quantified: root length, aerial dry weight, root dry weight, concentration of cadmium in the tissues, efficiencies of absorption, translocation and phytoextraction of cadmium. In addition, the soil and rhizosphere were evaluated for pH and electrical conductivity. It was found that the CCN-51 genotype obtained the best chlorophyll index, (42.23, 44.71, 48.76 and 41.91 Spad units) greater root length (15.72 cm), cadmium concentration in the aerial part (6.94 mg kg-1), absorption efficiencies (61.59 µg g-1), translocation (13.85 µg g-1) and cadmium phytoextraction (57.46 µg g-1), while EET-103 obtained the best root cadmium concentration (4.91 mg kg-1), the highest pH (5.74) and electrical conductivity of the soil (3.45 dS m-1). Regarding the effect of cocoa genotypes with macronutrient fertilization, it was evidenced that the application of NPKSMgCa significantly increases the concentration of Cd in the aerial part of CCN-51 (9.5 mg Kg-1) and EET-103 (7.67 mg Kg-1). In addition, it increases the efficiency of cadmium fioextraction (81.29 and 67.77 µg g-1) in (CNN-51 and EET-103). The fertilization with macronutrients increases the acidity and salinity of the soil, this causes an increase in the bioavailability and absorption of Cd in the plants, significantly raising the concentration of Cd in the aerial tissues of the cocoa plants. Furthermore, this reduces the chlorophyll concentration and dry mass production in the morphological components.